3 - Le financement de l’éducation dans les collectivités locales, quels défis ? - Dembélé, Marie Elisabeth (Africa Development, 2021)
This article aims to analyse the support provided by the state to local collectivities in Mali, to target the expenditure categories included in the funding and observe their appropriation by the beneficiaries of education services. A sample of 20 communes based in five regions was selected to analyse the structure of budgetary allocations from 2007 to 2012, in terms of expenditure categories and appropriation for direct and indirect beneficiaries. Similarly, the change in the number of learners, teachers and the number of educational institutions was analysed in order to clarify the link with the change in the budget. The budget analysis showed that at least 84 per cent of funding was allocated to indirect beneficiaries, namely teachers and staff of the school administration, while only 16 per cent went to learners and their parents – direct beneficiaries: here lies the contradiction that prompted this publication. The article attempts to introduce the debate on this inequality which appears to be a determining factor in achieving the goals of Education for All (EFA). Some suggestions for advocacy and engagement with decision- makers were made. Finally, this publication reminds decision-makers of the need to consider the increase in the number of learners, teachers and the number of schools in education financing. Local collectivities can direct their efforts towards the declining expenditure categories, to complement the efforts of the state through the Finance Law – the state budget.